Geospatial Technologies in Environmental Management - Hoalst-Pullen, Nancy; Patterson, Mark W.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The book explores new approaches and applications of geospatial technologies to understand past, present and future impacts environmental policies and management practices have on the landscape. From forestry to water use, and from wildlife management to agricultural practices, this collection of case studies examines the application of geospatial technologies in managing natural resources, land use, and environmental systems. These case studies are current and written by leading international geospatial technology practitioners. They also incorporate the causative and resultant roles of environmental policies and management within a geospatial context. The book is scientific and research-oriented, yet appealing to a broad audience interested in environmental applications of geospatial technologies, thus making it an important reference source for the fields of GIS, remote sensing, geography, environmental policy and environmental science.
Wilderness and Wildlife Response -- Geotechnologies in Environmental Management -- Modeling Post-Eruption Habitat Changes for Deer at Mount St. Helens using Remote Sensing and GIS -- Pyrogeography: Mapping and Understanding the Spatial Patterns of Wildfire -- Assisting Natural Resource Management in Mammoth Cave National Park Using Geospatial Technology -- Glaciers -- Geospatial Techniques to Assess High Mountain Hazards: A Case Study on California Rock Glacier and an Application for Management in the Andes -- Glacier Inventory: A Case in Semiarid Chile -- Wetlands and Watersheds -- Employing a Geographic Information System for Wetlands Management in Nebraska$1 (Bs Rainwater Basin -- The Effects of Land Cover Change: Increasing Watershed Imperviousness in Kentucky -- Exploring the Spatially Varying Impact of Urbanization on Water Quality in Eastern Massachusetts Using Geographically Weighted Regression -- Human Health and the Environment -- Application of GIS in Evaluating the Potential Impacts of Land Application of Biosolids on Human Health -- Remote Sensing, Public Health & Disaster Mitigation.s
Keywords: Geography; Remote sensing; Geographical information systems; Environmental management; Geography; Geographical Information Systems/Cartography.; Environmental Management; Remote Sensing/Photogrammetry.